22 UMPSA graduates from the first cohort of Bachelor of Science in Applied Data Analytics - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2023)
GAMBANG, 24 October 2023 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) successfully produced 22 graduates from the first cohort of the Bachelor of Science in Applied Data Analytics with Honours programme during the 18th Convocation Ceremony of UMPSA held recently.